Política de formação continuada de professores em escolas da rede pública municipal de ensino de Sorriso-MT : implicações entre formação e trabalho docente - Silva, Edna Coimbra da (2014)
This research is situated in the field of teacher formation, delimiting as object of study the policy of continuing formation of teachers of the public schools of the city of Sorriso-MT and its implications to the docent work, in the years of 2012 to 2013. The research is oriented by the following questioning: How does the continuing formation of teachers of the public schools of the city of Sorriso-MT occur and which is its implication to the constitution of the docent work? This questioning allowed comprehending how the continuing formation is happening in the public schools of the city of Sorriso-MT and where is the place of the teacher in this policy. In the theoretical-methodological options, the research is ruled in the cycle of policies of Ball (2001, 2005, 2006). This author emphasizes the policy as being a continuum cycle, in which three contexts are featured: context of influence, of text and of practice. This study intends to cover the cycle of policy of continuing formation of teacher of the public schools. The methodology of the research has a qualitative perspective, with data gathering through bibliographic study, documental study and interviews with the subjects involved in the continuing formation during the period and place delimited. In the analysis, it is considered that the continuing formation is a process of theoretical-practical construction, which is constructed in the trajectory of the professional life of the teacher. The result of the study of the documents and interviews analyzed indicates that the policies, of the continuing formation of the teacher of the public schools of Sorriso-MT, are composed of several programs coming from the federal and city government and from private institutions. Among the initiatives, the project “Teacher’s Room” is featured, it is a formation in locus which aims to give to the teacher opportunities of a formation that helps in his work, allowing the teacher to be the protagonist in his formation, which strengthen the docent work, but in the same time, has perspectives that could characterize as managerial influences. In this way, I conclude that the continuing formation of teachers of the public schools of the city of Sorriso- MT is hybrid under influence of the contradictory process of the formation. The project “Teacher’s Room” in some aspects reinforce the technization of the teaching and makes the docent responsible, which it is configured in the process of the docent disprofissionalization through the technization of the teaching. Although in other aspects, it collaborates to strengthen of the docent work through the contribution to the work and the docent autonomy when it is ruled in the collective study of teachers aiming to serve their professional necessities. We observed that this policy of continuing formation of teachers may be powerful if there is a distancing from the managerial perspective and is the approximates to the collective study which considers the theory and the practice of the docent formation as a way in the construction of actions intending to strengthen the docent work.